1989
DOI: 10.1159/000174496
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Treadmill Exercise Data in Patients with Atrial Fibrillation

Abstract: Serial submaximal treadmill tests are often used to evaluate the efficacy of therapy in patients with atrial fibrillation. Since the response to serial tests can be influenced by a ‘learning phenomenon’, we performed maximal exercise tests on 9 patients (mean age 63 ± 4 years) with chronic atrial fibrillation. Points of analysis for the initial and follow-up treadmill exercise tests were 3 mph/0% grade, the gas exchange anaerobic threshold, and maximal exertion. Significant (p < 0.05) reductions in ventilation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The second test was used in the analysis, as research has shown a significant “learning effect” after the first test,10 11 which appears to abate after the second test 12 13. Post-MI subjects performed their tests in the Physiotherapy Department at Kent and Canterbury Hospital, UK, and non-cardiac subjects in the BASES-accredited Sport Science Physiology Laboratory at Canterbury Christ Church University, UK.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second test was used in the analysis, as research has shown a significant “learning effect” after the first test,10 11 which appears to abate after the second test 12 13. Post-MI subjects performed their tests in the Physiotherapy Department at Kent and Canterbury Hospital, UK, and non-cardiac subjects in the BASES-accredited Sport Science Physiology Laboratory at Canterbury Christ Church University, UK.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, non-cardiac subjects only completed a treadmill test using similar protocol to the SWT. Each subject was familiarised with the test and performed two tests, which should have been sufficient to substantially reduce any learning effect;12 13 the second was used in the analysis. The treadmill and SWT were performed in random order as determined by computer.…”
Section: Methodsmentioning
confidence: 99%